Morbidity pattern at the National Youth Service Corp camps in Nigeria - Emorinken, Airenakho; Aikhuomogbe, Onosegbe; Eigbe, Bezaleel; Usman, Sarah; Isuekebhor, Cynthia (International Journal Of Community Medicine And Public Health, 2022)
Background: The National Youth Service Corps (NYSC) was designed to foster shared bonds among Nigerian youths and promote national unity. The orientation course is one of the program’s key initiatives. Even though camping promotes socialization and self-confidence, campers may be exposed to a variety of diseases and injuries. This study aimed to evaluate the pattern of diseases seen in the NYSC orientation camps. Methods: This was a descriptive cross-sectional study conducted in NYSC orientation camps in Delta, Abia, and Katsina States. The demographic information and diagnoses were extracted from the camp clinics' registers. The data was analysed with SPSS, and the level of significance was set at p<0.05. Results: A total of 2231 cases were seen. There were 299 cases (13.4%) seen in Delta state camp, 1076 (48.2%) from Abia, and 856 (38.4%) from Katsina state. There were more males (51.7%) than females (48.3%). The mean age was 25.10±2.67 years. The most common diagnoses were upper respiratory tract infection (23.4%), malaria (22.5%), acid-peptic disorders (12.1%), gastroenteritis (6.9%), musculoskeletal disorders (4.7%), and allergic diseases (4.7%). Fatigue/myalgia, headache disorders, and malingering accounted for 4.3%, 3.8%, and 1% of cases, respectively. Bronchial asthma and sexually transmitted infections were significantly more common in females than males (p<0.001). Conclusions: This study indicated that orientation camps are home to a variety of diseases, with upper respiratory tract infections and malaria being the most prevalent. This information is essential for resource allocation, planning, and policy formulation.